2013
DOI: 10.1002/bjs.9039
|View full text |Cite
|
Sign up to set email alerts
|

Use of surgical-site infection rates to rank hospital performance across several types of surgery

Abstract: When comparing SSI rates in all operations, differences between hospitals were explained by case mix. For individual types of surgery, case mix varied less between hospitals, and differences were explained largely by random variation. Although SSI rates may be used for monitoring quality improvement within hospitals, they should not be used for ranking hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…27 Numerous studies have also shown variability in riskadjusted patient outcomes across different hospitals and across different procedures, including bariatric surgery. 21,[28][29][30][31] Programs such as the National Surgical Quality Improvement Program have been shown to reduce complication rates at participating hospitals and have proven both cost-effective and cost-saving.…”
Section: Discussionmentioning
confidence: 99%
“…27 Numerous studies have also shown variability in riskadjusted patient outcomes across different hospitals and across different procedures, including bariatric surgery. 21,[28][29][30][31] Programs such as the National Surgical Quality Improvement Program have been shown to reduce complication rates at participating hospitals and have proven both cost-effective and cost-saving.…”
Section: Discussionmentioning
confidence: 99%
“…17 These data confirm that crude SSI rates do not reliably reflect trends or enable interhospital comparison. 31 For CABG and orthopedic procedures, although our crude SSI rates were similar to adjusted rates for risk index category 1, a large number of patients were classified as risk index category 2, where SSI rates were~50% higher. A crude rate would not adequately convey this increase in risk.…”
Section: Discussionmentioning
confidence: 52%
“…For example, van Dishoeck et al 21 found a rankability of 80% for surgical-site infection (SSI) after colonic resection but 0% for caesarean section. Rankability was 8% in all operations combined, as the differences in SSI rates were explained mainly by case mix.…”
Section: Discussionmentioning
confidence: 99%